2020
DOI: 10.1101/2020.04.05.024984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpretable machine learning framework reveals novel gut microbiome features in predicting type 2 diabetes

Abstract: New interpretable machine-learning analytic framework identifies a combination 55 of microbes consistently associated with type 2 diabetes risk across three 56 independent cohorts involving 9111 participants 57 • Faecal microbiota transplantation from humans to germ-free mice demonstrates a 58 causal role of the identified combination of microbes in the type 2 diabetes 59 development 60 • Body shape could modify the gut microbiome-diabetes relationship 61 4 Abstract 62Gut microbiome targets for type 2 diabetes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Most of the current studies describing the role of bacteria in diabetes have been case-control studies, with diabetes being a binary trait defined by setting a cutoff to some continuous glucose measure ( 3 , 4 , 12 ). Type 2 diabetes, however, is a disease preceded by a long-lasting prediabetic state, and the development of the disease is a continuous process ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current studies describing the role of bacteria in diabetes have been case-control studies, with diabetes being a binary trait defined by setting a cutoff to some continuous glucose measure ( 3 , 4 , 12 ). Type 2 diabetes, however, is a disease preceded by a long-lasting prediabetic state, and the development of the disease is a continuous process ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Gou et al ( 12 ) used a similar interpretable machine learning strategy and found bacteria that effectively differentiated type 2 diabetes cases from healthy controls in the Chinese population. Additionally, they built a microbiome risk score (MRS) and showed the causal role of identified bacteria on diabetes development after fecal microbiota transplantation to mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the work by Gou et al (12), the main reasons behind these inconsistencies are likely study design and population structure. We are not aware of any population with similar follow-up period and where microbiome data is available and oral glucose tolerance test has been carried out at the baseline and at the follow-up.…”
Section: Discussionmentioning
confidence: 96%
“…Most of the current studies describing the role of bacteria in diabetes have been case-control studies with diabetes being a binary trait defined by setting a cut-off to some continuous glucose measure (3,4,12). Type 2 diabetes however is a disease preceded by a long-lasting prediabetic state and the development of the disease is a continuous process (13).…”
Section: Discussionmentioning
confidence: 99%
“…For g_Streptococcus, it has been reported that diabetes is the most frequently identi ed risk factors in invasive Streptococcus agalactiae (GBS) infections [53]. Recent machine learning studies have found that f_Mogibacteriaceae is one of the markers that can effectively predict the risk of DM [54]. Ruminococcus.spp was positively associated with DM in many studies [55][56][57][58][59].…”
Section: Interpretation Of Outputmentioning
confidence: 99%